Multi‐analysis strategy for metabolism of Andrographis paniculata in rat using liquid chromatography/quadrupole time‐of‐flight mass spectrometry. (18th November 2014) - Li, Wenlan; Sun, Xiangming; Xu, Ying; Wang, Xuezhi; Bai, Jing; Ji, Yubin
Abstract Compared with chemical drugs, it is a huge challenge to identify active ingredients of multicomponent traditional Chinese medicine (TCM). For most TCMs, metabolism investigation of absorbed constituents is a feasible way to clarify the active material basis. Although Andrographis paniculata (AP) has been extensively researched by domestic and foreign scholars, its metabolism has seldom been fully addressed to date. In this paper, high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry was applied to analysis and characterization of AP metabolism in rat urine and feces samples after oral administration of ethanol extract. The differences in metabolites and metabolic pathways between the two biological samples were further compared. The chemical structures of 20 components were tentatively identified from drug‐treated biological samples, including six prototype components and 14 metabolites, which underwent such main metabolic pathways as hydrolyzation, hydrogenation, dehydroxylation, deoxygenation, methylation, glucuronidation, sulfonation and sulfation. Two co‐existing components were found in urine and feces samples, suggesting that some ingredients' metabolic processes were not unique. This study provides a comprehensive report on the metabolism of AP in rats, which will be helpful for understanding its mechanism. Copyright © 2014 John Wiley & Sons, Ltd.